A remarkable new genus and species of Euryproctini (Hymenoptera: Ichneumonidae, Ctenopelmatinae) from Thailand - Reshchikov, Alexey; Quicke, Donald L.J.; Butcher, Buntika A. (European Journal of Taxonomy, 2022)
Rhytidaphora Reshchikov & Quicke gen. nov. (type species Rhytidaphora thailandica Reshchikov & Quicke gen. et sp. nov.) from Thailand is described and illustrated. It belongs to the tribe Euryproctini of the subfamily Ctenopelmatinae (Hymenoptera, Ichneumonidae) based on the absence of glymma and the subapical notch on the ovipositor. The new taxon differs from all other genera of Euryproctini by the occipital carina being broadly incomplete dorsally, the hypostomal carina joining the occipital carina shortly before the base of the mandible, distinctly pectinate tarsal claws, and immovably fused and strongly sculptured second and third metasomal tergites.